PETA KONSEP SEBAGAI UPAYA UNTUK MENINGKATKAN MAKNA PEMBELAJARAN IPS GEOGRAFI DI SEKOLAH - Tjahyono, Heri (Universitas Negeri Semarang, 2008)
The aplication of curricullum which is based on Competence Standart (SK) andCompetence Based (KD) demands the student to be independent, in order for them tobe able to develop their ability in their ways of thinking and to be independenly active.There fore, teachers as motivators need to create a condusive atmosphere in teachingand learning activities. For example they may apply new teaching methods whichallow the student to think creatively, actively and independently. The newest teachingand learning methods or models suggest the teachers to apply a conceptual map withinthe material given. Through a conceptual map, both the students and the teacher willbe assisted to get the Ã¢â¬ÅmeaningÃ¢â¬Â of the related material. Besides, it can also give asystematical guidance based on geography subject according to the topic, sub topicand other related topics in order to keep the material going on the right track. Theconcept map may be applied to analyze students acquisition toward the learnedconcept in more detailed than a test, such as the amount of the acquired concept, thedepth, the extention, and the entive of acquisition of a topic. The point is, the conceptmap may function as an effective evaluation device.Kata kunci: peta konsep, makna pembelajaran, geografi.